Pengembangan Sistem Informasi E-Ternak Banyuwangi (E-Nak Wangi) berbasis Android (Studi Kasus: Dinas Pertanian dan Pangan Kabupaten Banyuwangi) - Muhammad Sultan Alfariz; Denny Sagita Rusdianto; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Dinas Pertanian dan Pangan Kabupaten Banyuwangi is an agency that takes care of cattle in the area of ​​Banyuwangi Regency. Based on data obtained from Dinas Pertanian dan Pangan Kabupaten Banyuwangi, the number of cattle population in Banyuwangi Regency reached 126,114 cows. The problems that occur in the Banyuwangi Regency Agriculture and Food Department are in the data collection of cattle with a population that reaches 126,114 cows, the risk of loss of paper sheets that contain curriculum data and cattle photo files that have been taken by the data and negligence of officers in conducting data collection, service And cattle monitoring and officers have obstacles to find the location of the cattle that will be taken by the data, because the owners of cattle animals cannot provide information on cattle owned to the officers. Based on these problems the author gave a solution in the form of the development of the Banyuwangi E-Livestock System (E-NAK Wangi) based on Android, it is expected to overcome and reduce the problems that exist in Dinas Pertanian dan Pangan Kabupaten Banyuwangi the process of collecting cattle animals and providing cattle animal services which has been registered. System development is done using waterfall development methods with stages starting from the requirements stage, design, implementation, testing and deployment & maintenance. At the engineering stage and the need for analysis is obtained 28 functional requirements and 3 types of actors. Implementation Using Java Programming Language on Android Studio Software. The testing carried out in the form of unit testing based on 3 test samples resulted in valid results, integration testing resulted in valid results, and testing validation gots 100% valid than 49 test cases.